A Numerical Investigation on Burgers Equation by MOL-GPS Method - Hashemi, M. S.; İnç, Mustafa; Karatas, E.; Akgul, A. (Amer Scientific Publishers, 2017)
Group preserving scheme for calculating the numerical solutions of the Burgers equation with appropriate boundary and initial conditions is given in this work. Approximate solutions are demonstrated by tables and figures. Numerical results present the efficiency and power of this technique.
Keywords: Burgers Equation; Method of Line; Group Preserving Scheme